Well-Distributed Polysilsesquioxane-Modified Carbon Nanotubes for Thermal Conductive Insulating Silicone Rubbers - Long Han; Zhaobo Wang; Jing Hua; Jieting Geng (Advances in Polymer Technology)
Despite carbon nanotubes (CNTs) have garnered tremendous research interests for enhancing the electrical and thermal conductivity of polymers, it is still a considerable challenge to achieve the uniform dispersion of carbon nanotubes in polymer matrix. Herein, inspired by the mussel-inspired chemistry, we adopted the strategy of coating CNTs with polydopamine. And the polysilsesquioxane-modified CNTs (CNTs-PSQ) were obtained based on the click chemistry reaction. The FT-IR, Raman, XRD, and TGA collectively demonstrated the successful modification of PSQ on the surface of CNTs. The incorporation of PSQ could significantly improve the dispersion of CNTs in the silicon rubbers, and a strong interfacial interaction was formed between CNTs-PSQ and silicon rubber matrix, as observed from TEM images of silicon rubber/CNTs-PSQ nanocomposites. Meanwhile, compared with the nanocomposites with neat CNTs, the ones with CNTs-PSQ exhibited simultaneously improved electrical conductivity and insulating performance. This strategy proposed for the preparation of PSQ-modified CNTs provides insights toward highly insulating and thermal conducting polymers.